2019
DOI: 10.12973/eu-jer.8.4.1245
|View full text |Cite
|
Sign up to set email alerts
|

Motion Graphic Animation Videos to Improve the Learning Outcomes of Elementary School Students

Abstract: The purpose of this study was to investigate the effectiveness of the development of motion graphic animation video media in Natural Sciences subjects in Elementary Schools. This study uses a type of Research and Development research with quantitative tests. This study employed the experimental research method involving 27 students in the control group and 27 students in the experimental group. This research was conducted on 5th-grade students in elementary school in 2 different schools. Data collection uses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…The learning process in schools is oriented to increasing knowledge competence. Conventional learning with the lecture method is often used by teachers both at elementary and upper school levels (Hapsari et al, 2019). The learning resources and media used are in the form of textbooks and PowerPoint slides that contain descriptions of textual and rote material.…”
Section: Introductionmentioning
confidence: 99%
“…The learning process in schools is oriented to increasing knowledge competence. Conventional learning with the lecture method is often used by teachers both at elementary and upper school levels (Hapsari et al, 2019). The learning resources and media used are in the form of textbooks and PowerPoint slides that contain descriptions of textual and rote material.…”
Section: Introductionmentioning
confidence: 99%
“…Sefriani et al [51], in their research, also revealed that the use of interactive media or learning aids would be able to provide good results in learning, one of which could be realized by using computers in the learning process and collaborating with specific learning methods. Guan et al [52] & Ismail et al [53] also explained the appearance of learning programs with ICT-based media formats, especially computers and smartphones packaged in a digital book application program [54], interactive multimedia [28,53], animated videos [56], game based learning [57] could display interactivity and motivate students to be enthusiastic about participating in the learning process, so students would tend to find it easier to achieve competency.…”
Section: B Discussionmentioning
confidence: 99%
“…The use of ICT in learning activities is a must to improve student academic achievement [7,55]. The success of implementing digital technology into the learning process will significantly depend on the teachers" readiness and willingness to adopt technology, as well as teachers' understanding of the importance of ICT in the learning process in the digital era and during the pandemic currently hitting the world as it is today [27,56]. Through this technology, teachers can create a student-centered learning condition and make it easy for them to complete their work [60].…”
Section: B Discussionmentioning
confidence: 99%
“…Audio-visual material can only be meaningful if it is used as part of the teaching process. By using audio-visual media, students can utilize technology and media in a series of ways to enhance their learning as an alternative source for independent learning (Hapsari, Hanif, Gunarhadi, & Roemintoyo, 2019). Nevertheless, in the schools observed, both the teacher and other developers had never developed audio-visual media before.…”
Section: Downloaded Freementioning
confidence: 99%